High Air Humidity Causes Atmospheric Water Absorption via Assimilating Branches in the Deep-Rooted Tree Haloxylon ammodendron in an Arid Desert Region of Northwest China - Gong, Xue-Wei; Lü, Guang-Hui; He, Xue-Min; Sarkar, Binoy; Yang, Xiao-Dong (Frontiers in Plant Science, 2019)
Atmospheric water is one of the main water resources for plants in arid ecosystems. However, whether deep-rooted, tomentum-less desert trees can absorb atmospheric water via aerial organs and transport the water into their bodies remains poorly understood. In the present study, a woody, deep-rooted, tomentum-less plant, Haloxylon ammodendron (C.A. Mey.) Bunge, was selected as the experimental object to investigate the preconditions for and consequences of foliar water uptake. Plant water status, gas exchange and 18O isotopic signatures of the plant were investigated following a typical rainfall pulse and a high-humidity exposure experiment. The results showed that a high content of atmospheric water was the prerequisite for foliar water uptake by H. ammodendron in the arid desert region. After atmospheric water was absorbed via the assimilating branches, which perform the function of leaves due to leaf degeneration, the plant transported the water to the secondary branches and trunk stems, but not to the taproot xylem or the soil, based on the 18O isotopic signatures of the specimen. Foliar water uptake altered the plant water status and gas exchange-related traits, i.e., water potential, stomatal conductance, transpiration rate and instantaneous water use efficiency. Our results suggest that atmospheric water might be a subsidiary water resource for sustaining the survival and growth of deep-rooted plants in arid desert regions. These findings contribute to the knowledge of plant water physiology and restoration of desert plants in the arid regions of the planet.